1988
DOI: 10.1107/s0108270188001830
|View full text |Cite
|
Sign up to set email alerts
|

The structure of [Au-μ-{3,5-(C6H5)2C3HN2}]3Cl2: a trinuclear mixed-valence gold pyrazolate complex

Abstract: Abstract.Tris-/~-(3,5-diphenyl-1-pyrazolyl-N,N')-di-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The core of the molecule is formed by three gold atoms bridged through three exobidentate pyrazolate groups, forming a nine-membered ring (Figure ). This gold−pyrazolate macrocycle is not uncommon in the chemistry of group 11 metals; similar situations have been reported for the related (carbenato)gold(I) complex [Au{C(OEt)N(C 6 H 4 Me)}] 3 or the (pyrazolato)gold(I) complexes [Au(μ-3,5-(CF 3 ) 2 Pz)] 3 10b and [Au(μ- 3,5-Ph 2 Pz)] 3 , for the heterovalent Au(I)/Au(III) compounds [{Au(μ-3,5-Ph 2 Pz)} 3 Cl 2 ] and [{Au(μ-3,5-Ph 2 -4-ClPz)} 3 Cl 2 ], , and for the closely related silver(I) analogue [Ag(μ-3,5-Ph 2 Pz)] 3 . In 5 , as in all the previous structures (except [Au(μ-3,5-Ph 2 Pz)] 3 , which exhibits intramolecular crystallographically imposed symmetry), the metallacycle is not strictly planar, but slightly irregular and puckered.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The core of the molecule is formed by three gold atoms bridged through three exobidentate pyrazolate groups, forming a nine-membered ring (Figure ). This gold−pyrazolate macrocycle is not uncommon in the chemistry of group 11 metals; similar situations have been reported for the related (carbenato)gold(I) complex [Au{C(OEt)N(C 6 H 4 Me)}] 3 or the (pyrazolato)gold(I) complexes [Au(μ-3,5-(CF 3 ) 2 Pz)] 3 10b and [Au(μ- 3,5-Ph 2 Pz)] 3 , for the heterovalent Au(I)/Au(III) compounds [{Au(μ-3,5-Ph 2 Pz)} 3 Cl 2 ] and [{Au(μ-3,5-Ph 2 -4-ClPz)} 3 Cl 2 ], , and for the closely related silver(I) analogue [Ag(μ-3,5-Ph 2 Pz)] 3 . In 5 , as in all the previous structures (except [Au(μ-3,5-Ph 2 Pz)] 3 , which exhibits intramolecular crystallographically imposed symmetry), the metallacycle is not strictly planar, but slightly irregular and puckered.…”
Section: Resultssupporting
confidence: 72%
“…The observed N−Au lengths range between 1.99(2) and 2.07(2) Å, with mean values of 2.01 and 2.03(1) Å for both independent molecules. These values are longer than those reported for the CF 3 analogue,10b 1.93(3) Å, but statistically indistinguishable from the Au−N bond distances described in complexes containing phenyl-substituted pyrazolate ligands (range 1.978(9)−2.05(2) Å). ,, The pyrazolate rings and the phenyl groups maintain strict planarity and do not deserve further comment.…”
Section: Resultsmentioning
confidence: 50%
“…The reaction of Au 3 (3,5-Ph 2 Pz) 3 with aqua regia afforded the partially oxidized product Au 3 (3,5-Ph 2 Pz) 3 Cl 2 , in which one of the three Au­(I) ions was oxidized to Au­(III) . This mixed-valence Au­(I) 2 Au­(III) CTC can also be synthesized by the direct reaction of Au­(pyridine)­Cl 3 with Na­(3,5-Ph 2 Pz) in a THF solution . In 2002, Raptis et al reported the X-ray crystal structures of Au­(I)­Au­(III) 2 and Au­(III) 3 species from the oxidation reactions of Au 3 (3,5-Me 2 Pz) 3 with aqua regia …”
Section: Synthesis and Reactivitymentioning
confidence: 99%
“…These kinds of ligands have a proven ability to hold metal atoms in close proximity while permitting a wide range of intermetallic separations, being useful in the synthesis of shape-persistent macrocycles, such as the homonuclear [M I A C H T U N G T R E N N U N G (m-Rpz)] 3 (M = Cu, [36][37][38][39][40][41][42] Ag, [37,38,43,44] Au; [43,[45][46][47][48][49][50] Rpz = pyrazolate or substituted pyrazolate) or [M II 3 A C H T U N G T R E N N U N G (m-Rpz) 6 ] (M II = Pd [51,52] Pt [52,53] ) as the heteronuclear clusters [Pd 2 M 2 A C H T U N G T R E N N U N G (m-Rpz) 6 ] (M = Cu, Ag, Au), [52,54] and [M 2 M' 4 A C H T U N G T R E N N U N G (m-Rpz) 8 ] (M = Pd, Pt; M' = Cu, Ag). [52,55] Apart from the interest arising from their structural diversity, some of these pyrazolate bridging complexes have also been shown to be excellent systems for examining metallophilic interactions [49,[56][57][58][59][60][61][62] and as luminescent materials.…”
Section: ) Lm'ct Transitions P-a C H T U N G T R E N N U N G (Dmpz)!mmentioning
confidence: 99%